HISTORICAL INITIATIVE: THE SPIRITUAL CODE FOR PROMOTING CHINESE MODERNIZATION - Han, J. (Farabi Journal of Social Sciences, 2023)
The 20th National Congress of the CPC has put forward a mission for a new era and a new journey, promoting the great rejuvenation of the Chinese nation through Chinese modernization. The CPC has led the people of all ethnic groups in the country towards this major achievement at great cost through long-term exploration and practice. The Historical Initiative is the strong spiritual support and spiritual power that promotes Chinese modernization. Its role is based on the essential characteristics of Chinese modernization. The historical initiative is embodied in grasping the historical trend, following the historical laws, undertaking the historical mission, and sublimating the historical model in the great practice of promoting Chinese modernization. In order to embark on a new journey and promote Chinese modernization, it is necessary to deeply understand the spiritual code of the historical initiative. This can be achieved by taking the leadership of the CPC as the fundamental guarantee, adhering to the basic principle of independence, daring to fight, being good at fighting, and carrying forward the spirit of the historical initiative to open up new possibilities for career development. Keywords: CPC, Historical Initiative, Chinese Modernization, the great rejuvenation of the Chinese nation.